Study on hybrid fibre reinforced UHPC beams under single and repeated lateral impact loading. (3rd March 2023) - Wei, Jie; Li, Jun; Wu, Chengqing
Graphical abstract: Highlights: Reinforced UHPC beams are tested against repeated impact loads. UHPC constitutive model and bond-slip behaviour are considered in the numerical analysis. Energy evolution diagram, dynamic shear force and bending moment distribution diagram are discussed. Failure mechanism of UHPC beam under repeated impact load are evaluated in the parametric study. Abstract: This paper investigates the dynamic response of hybrid fibre reinforced ultra-high performance concrete (UHPC) beams against single and repeated low-velocity impact loads. A brief description of the drop weight impact tests on the UHPC beams was presented first followed by the development of the material and structural model in finite element analysis. A plasticity-based concrete material model with validated compressive and tensile strength surface and damage algorithm was adopted for hybrid fibre reinforced UHPC material. Based on the test results, the bond-slip behaviour between steel rebar and UHPC matrix was developed in an empirical form and incorporated in the model. Compared to the model with the bond-slip definition, the model with perfect bonding was found to underestimate the maximum mid-span deflection, which highlighted the necessity of considering the bond-slip behaviour in dynamic analysis where large deflection occurs. The repeated impact tests were performed numerically, and the results were validated with experimental data. A parametric study was then performed to investigate the effect of key parameters, including different impact energy and the same impact energy but different impact numbers. The results indicated when the total energy increased, the repeated impact loads became more hazardous than the single impact load. With the validated model, the dynamic shear force and bending moment distribution diagrams were compared to study the failure mechanism in single and repeated impact loads.